Literacy Culture Development in Improving Students' Reading Interest (Case study of SMA Negeri Banguntapan Yogyakarta) - Charneidy, Muhammad Avryzal; Robani, Muhammad Arif; Nugraheni, Yumidiana Tya (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to analyze the development of literacy culture in increasing students' reading interest in SMA Negeri Banguntapan Yogyakarta. The method used is a case study with a qualitative approach, where data is collected through interviews, observations, and document analysis related to literacy programs in schools. The results of the study indicate that the implementation of various literacy activities, such as reading clubs, writing competitions, and book discussions, has succeeded in attracting students' attention and increasing their reading interest. In addition, support from teachers and the use of comfortable reading rooms also contribute positively to the literacy culture in schools. This study is expected to provide insight for schools and educators in designing more effective programs to increase students' reading interest, so that literacy culture can be embedded well in everyday life.